Pre-hospital emergency response to terrorist attacks: A scoping review. Issue 1 (January 2022) - Amiresmaili, Mohammadreza; Talebian, Ali; Miraki, Sadegh
Background: Terrorist incidents are on the rise in the world, and many countries have been involved so far. Unfortunately, many innocent people fall victim to such incidents every year. The pre-hospital emergency, as one of the most important organs in the management and service of the victims, plays a vital role in these events. Objectives: This scoping review aimed to evaluate the performance and preparedness of the pre-hospital emergency in the world for such Terrorist incidents. Methods: In order to access the documents and scientific evidence relevant to the purpose of our research, selected keywords were searched in PubMed, Scopus, and Web of Science databases. Finally, we collected the required information through a pre-designed data extraction form that designed based on the purpose of this study. Results: The initial search, with the specified search strategies, resulted into 794 documents (263, 488, and 43 documents from PubMed, Scopus, and Web of Science databases, respectively). Finally, eight papers were selected through the full text of the selected articles, three of which were qualitative and three were quantitative, and two were mix-methods (qualitative/quantitative). Our findings show that published papers have so far emphasized four main axes, namely, preparation, training and practice, effective communication, and the proper triage and transmission of these four axes. Conclusion: A few studies have been done in this area and more studies should be done in different areas and sectors, and given that terrorist incidents are on rise and the pre-hospital emergency organization as one of the most important organizations is not well prepared to respond these events although it has a vital role to play, they need to be more prepared to effectively manage these incidents.